Engaging learners through Zoom strategies for virtual teaching across disciplines - Brennan, Jonathan (Jossey-Bass, a Wiley imprint, 2021)
"Many educators are frustrated with the perceived limitations of a video-conferencing platform like Zoom that was originally designed for corporate meetings. Yet Zoom offers tools that, with creativity and practice, can be used to more deeply engage students, reduce Zoom Fatigue, promote active learning, and achieve successful learning outcomes. Dr. Brennan has developed a collection of dozens of active, synchronous Zoom learning structures that can be used in any discipline, and at multiple levels of education. The resulting book, Engaging Learners through Zoom, will help educators leverage the latest research on active learning, engagement, learner motivation and cognitive neuroscience, to train them to be more effective as educators in distance learning, and to ensure that learners have the best possible opportunity to achieve their educational, career and life goals. This is especially important in ensuring equity in educational outcomes for students who are at greater risk of dropping out of high school, and who are the first in their families to attempt college. The goal for this book is to provide educators with a sizeable toolbox for improving distance learning experiences and results, primarily through synchronous learning. If educators use these tools with students, the author and his company, On Course, will achieve its goal of significantly increasing learner engagement and thus the opportunity for more students to achieve their educational goals" -- Provided by publisher.